2006
DOI: 10.1002/bdra.20322
|View full text |Cite
|
Sign up to set email alerts
|

Screening for novel PAX3 polymorphisms and risks of spina bifida

Abstract: BACKGROUND: PAX3 plays an important role in mammalian embryonic development. Known mutations in PAX3 are etiologically associated with Waardenburg syndrome and syndromic neural tube defects (NTDs). Mutations in the murine homologue, pax3, are responsible for the phenotype of splotch mice, in which nullizygotes are 100% penetrant for NTDs. METHODS: The study sample included 74 infants with spina bifida (cases) and 87 nonmalformed infant controls. The conserved paired-box domain as well as the upstream genomic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
(13 reference statements)
0
17
0
2
Order By: Relevance
“…Pax3 is expressed in the dorsal neuroepithelial cells along the entire anterior-posterior axis during the closure process (Goulding et al, 1991;Solloway and Robertson, 1999). A recent study suggests the association of PAX3 mutations with spina bifida in humans (Agopian et al, 2013), which was not found in early studies Lu et al, 2007). Pax3 homozygous mutant mouse embryos exhibit both spina bifida and exencephaly Epstein et al, 1991), whereas the latter is not seen in the β-catenin cKO mutant.…”
Section: Pax3 Mediates β-Catenin Signaling For Caudal Neural Tube Clomentioning
confidence: 85%
“…Pax3 is expressed in the dorsal neuroepithelial cells along the entire anterior-posterior axis during the closure process (Goulding et al, 1991;Solloway and Robertson, 1999). A recent study suggests the association of PAX3 mutations with spina bifida in humans (Agopian et al, 2013), which was not found in early studies Lu et al, 2007). Pax3 homozygous mutant mouse embryos exhibit both spina bifida and exencephaly Epstein et al, 1991), whereas the latter is not seen in the β-catenin cKO mutant.…”
Section: Pax3 Mediates β-Catenin Signaling For Caudal Neural Tube Clomentioning
confidence: 85%
“…However, screening of NTD populations for mutations in PAX3 or for association with particular SNP haplotypes does not suggest that PAX3 is a major genetic component of human NTDs (Trembath et al, 1999;Lu et al, 2007). Although mutation of PAX3 seems capable of causing NTDs in humans as in mice, the relative contribution of such mutations to the overall burden of NTDs remains unclear.…”
Section: Pax3 and Human Neural Tube Defectsmentioning
confidence: 94%
“…NTDs in the Splotch mutant can be rescued with supplemental dietary folic acid or thymidine, indicating that folic acid prevents NTDs by rescuing de novo thymidylate synthesis in this mouse model (9,10). However, Pax3 has not been linked to human NTD pathogenesis in epidemiologic studies (13,14).…”
Section: Introductionmentioning
confidence: 99%